Circ_0099630 knockdown alleviates lipopolysaccharide-induced injuries of human periodontal ligament cells through the inhibition of TLR4 by releasing miR-409-3p - Hongyan Qi; Bing Han; Jin Che (BMC, 2023)
Abstract Background Periodontitis triggers tooth loss and affects the health of population worldwide. Emerging evidence hints that circular RNAs (circRNAs) are involved in various diseases, including periodontitis. This study aimed to investigate the role of circ_0099630 in the progression of periodontitis. Methods Periodontitis cell model was constructed by treating human periodontal ligament cells (HPDLCs) with lipopolysaccharide (LPS). Quantitative real-time PCR was used to analyze the expression of circ_0099630, microRNA-409-3p (miR-409-3p) and toll-like receptor 4 (TLR4) mRNA. Western blot was used for detecting protein levels of TLR4, cleaved-caspase 3, Bcl-2, CyclinD1 and NF-κB signaling markers. For function analyses, cell proliferation was assessed by CCK-8 assay and EdU assay. The releases of pro-inflammation factors were monitored by ELISA kits. The potential relationship between miR-409-3p and circ_0099630 or TLR4 was verified by dual-luciferase reporter assay, RIP assay and pull-down assay. Results The expression of circ_0099630 and TLR4 was elevated in periodontitis patients and LPS-treated HPDLCs. LPS induced HPDLC proliferation inhibition, apoptosis and inflammatory responses, while circ_0099630 knockdown or TLR4 knockdown alleviated these injuries. Besides, TLR4 overexpression reversed the inhibitory effect of circ_0099630 knockdown on LPS-induced HPDLC injuries. Mechanism analysis showed that circ_0099630 positively regulated TLR4 expression by acting as miR-409-3p sponge. MiR-409-3p restoration largely ameliorated LPS-induced HPDLC injuries by depleting TLR4. Moreover, LPS activated the NF-κB signaling pathway, while circ_0099630 knockdown inhibited the activity of NF-κB signaling via the miR-409-3p/TLR4 axis. Conclusion Circ_0099630 knockdown relieved LPS-induced HPDLC injury by miR-409-3p/TLR4 axis, suggesting that circ_0099630 might be a potential target for periodontitis treatment.